A compreensão de implícitos textuais nas canções de protesto social : uma alternativa na formação do leitor crítico - Santos, Adna Nascimento Alves (2015)
It has become imperative in the current context of Brazilian public school the reading practices as an agenda of constant reflection and research for alternatives that can contribute to the development of the reading comprehension in various levels of middle school students, given the Saeb data and Prova Brasil (2014), whose large-scale assessments showed difficulties of the students to select implicit information, inferring the meaning of a word or expression, among others; there by, indicating, serious deviations of understanding and the appropriation of the writing production, in the act of reading. Based on this fact, the present report has as a guiding objective to promote the formation of a proficient and critical reader through the analysis of Brazilian social protest songs in activities of reading and understanding the implicit textual, enabling recognize them as situated discursive practices in daily life that can contribute to the formation of active citizens in society. Was taken as theoretical support the studies of textual linguistics, the sociocultural perspective; using the sociointeractional language design, subject and text for which the textual and discursive understanding can only be understood when it exceeds the limits of decoding linguistic elements and reaches the horizons of mobilization of the socio-historical and cultural knowledge and reconstruction of these within a communication situation in a given context. Therefore, we used a qualitative research, with the methodological approach by the application of didactics sequence in a 9th grade of elementary school, that used the song of social protest genre as mediator. Taking into account the proposal prepared for the research and what was executed, it is possible to say that the understanding of the text work from the songs analysis is configured as a positive and effective alternatives, as the students found new forms of meanings construction for the studied texts. The results obtained from this work fulfilled the ultimate goal of this trajectory that is becoming theoretical and practical support for the development of a concrete tool for socialization of experienced knowledge: the Pedagogical Section, whose main purpose is to share successful experiences with other Portuguese-speaking teachers in teaching and in the reading learning process.